Характеристика елементів інфраструктури (частина 2) - Яковенко, Р. В.; Yakovenko, R. (My University, 2018)
Наведено характеристику різних елементів інфраструктури, таких як ярмарок, комерційно-посередницькі фірми, оптова база, оптовий магазин тощо. The characteristics of various elements of the infrastructure, such as the fair, commercial intermediary firms, the wholesale base, the wholesale store, etc. are given.
Characteristics of infrastructure elements (part 2)
Keywords: ярмарки; роздрібна торгівля; гуртова торгівля; комерційно-посередницькі фірми; оптова база; холдинг; fairs; retail trade; wholesale trade; commercial intermediary companies; wholesale base; holding